( scientific ) تحليل الكتاب المدرسي للغة العربية في المرحلة الإبتدائية بمدخل العلمي - Rizqa, Sarita; Mahmud, Salami; Safariah, Safariah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
This study aims to determine appropriateness of Arabic textbooks at 2013 curriculum of Madrasah Ibtidaiyah in the scientific approach published by the Ministry of Religion which adjusted to the standards of the scientific approach and the standard of textbooks have been set. The research method is a description of qualitative method ( not in the form of numbers). The method used to collect data is a documentary method, for the document information researches are using an instrument which called content analysis. The results of the study, books published by the Ministry of Religion are still many errors in arabic language textbooks at the 5th grade Madrasah, both standard textbooks and substances. The various imporvements are needed to be used as textbook materials.